2000
DOI: 10.1067/mcp.2000.109356
|View full text |Cite
|
Sign up to set email alerts
|

Faster clearance of sustained release verapamil in men versus women: Continuing observations on sex-specific differences after oral administration of verapamil

Abstract: Pharmacokinetic studies after administration of 120 mg oral sustained- and regular-release racemic verapamil were performed in 13 healthy subjects (seven men, age 74 +/- 4 years [mean +/- SD], weight 69.9 +/- 5.4 kg, and body mass index 24.6 +/- 2.2]; and six women, age 65 +/- 13 years, weight 65 +/- 9.9 kg, and body mass index 25.3 +/- 3). Verapamil was measured by HPLC, concentration versus time data analyzed by noncompartmental models, and statistical analyses performed by ANOVA for repeated measurements. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 45 publications
0
25
1
2
Order By: Relevance
“…10 These data are in contrast to those in previous reports of faster Cl of i.v.-administerd racemic verapamil, Rverapamil and S-verapamil, and i.v.-administered erythromycin in women compared with men. 11 Krecic-Shepard et al 10 explained that the reasons for these different results include individual variations, alternative pathways in the metabolism of CYP3A4 substrates, route of drug administration, and differences in competition for transport mechanisms. Thus, they suggested a need for investigation of not only pathway-specific probes but also multiple routes of administration and formulation when studying differences in human subgroups or for elucidating dosing guidelines in human beings.…”
Section: Calcium-channel Blockerscontrasting
confidence: 85%
“…10 These data are in contrast to those in previous reports of faster Cl of i.v.-administerd racemic verapamil, Rverapamil and S-verapamil, and i.v.-administered erythromycin in women compared with men. 11 Krecic-Shepard et al 10 explained that the reasons for these different results include individual variations, alternative pathways in the metabolism of CYP3A4 substrates, route of drug administration, and differences in competition for transport mechanisms. Thus, they suggested a need for investigation of not only pathway-specific probes but also multiple routes of administration and formulation when studying differences in human subgroups or for elucidating dosing guidelines in human beings.…”
Section: Calcium-channel Blockerscontrasting
confidence: 85%
“…In contrast, the clearance of orally administrated verapamil is smaller in women than in men, suggesting that intestinal processes are a factor in the sex differences of drug clearance. 30,31) One possible explanation for this contradiction is higher CYP3A activity in the intestinal mucosa, but a recent study by Paine and coworkers found no significant difference between the sexes. 32) In terms of substrates, inducers and tissue specificity, P-glycoprotein (P-gp) has extensive overlap with CYP3A.…”
Section: Sex Difference Of Cyp3a4mentioning
confidence: 87%
“…More information is available on sex-related differences in drug absorption and bioavailability. For example, orally administered verapamil is cleared faster in men than women, a difference that is not observed after intravenous administration of this drug, suggesting that intestinal processes modulate sex-specific differences in verapamil pharmacokinetics (Krecic-Shepard et al, 2000). Ferrous sulfate absorption, measured with the aid of radioisotope labeling, is higher in prepubertal girls than boys (Woodhead et al, 1991), suggesting that hormonal differences may contribute to sex-based pharmacokinetic variability for this mineral salt (see also Section 3.1.3.6).…”
Section: Nutrient Bioavailabilitymentioning
confidence: 92%